The Impact of Gender Inequality in Education and Employment on Economic Growth : New Evidence for a Panel of Countries - Klasen, Stephan; Lamanna, Francesca (2012)
Using cross-country and panel regressions, we investigate to what extent gender gaps in education and employment (proxied using gender gaps in labor force participation) reduce economic growth. Using the most recent data and investigating an extended time period (1960-2000), we update the results of previous studies on education gaps on growth and extend the analysis to employment gaps using panel data. We find that gender gaps in education and employment considerably reduce economic growth. The combined "costs" of education and employment gaps in the Middle East and North Africa, and South Asia amount respectively to 0.9-1.7 and 0.1-1.6 percentage point differences in growth compared to East Asia. Gender gaps in employment appear to have an increasing effect on economic growth differences between regions, with the Middle East and North Africa, and South Asia suffering from slower growth in female employment.